2021
DOI: 10.1371/journal.pone.0249750
|View full text |Cite
|
Sign up to set email alerts
|

Optimal surgeon and hospital volume thresholds to reduce mortality and length of stay for CABG

Abstract: Objective We used nationwide population-based data to identify optimal hospital and surgeon volume thresholds and to discover the effects of these volume thresholds on operative mortality and length of stay (LOS) for coronary artery bypass surgery (CABG). Design Retrospective cohort study. Setting General acute care hospitals throughout Taiwan. Participants A total of 12,892 CABG patients admitted between 2011 and 2015 were extracted from Taiwan National Health Insurance claims data. Main Outcome Measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Often, complex procedures are not viable to provide in a small hospital as volumes at smaller sites may be insufficient to maintain high-level multidisciplinary skills yielding the best possible patient care and outcomes. [17][18][19][20] In reducing the work of patient movement, we may find that other systems have increased capacity for innovative work. Considering the transportation requirements for all transferred patients, a reduction in the number of patients being moved between sites will enable ambulance and patient transportation services to maintain focus on emergency response.…”
Section: Discussionmentioning
confidence: 99%
“…Often, complex procedures are not viable to provide in a small hospital as volumes at smaller sites may be insufficient to maintain high-level multidisciplinary skills yielding the best possible patient care and outcomes. [17][18][19][20] In reducing the work of patient movement, we may find that other systems have increased capacity for innovative work. Considering the transportation requirements for all transferred patients, a reduction in the number of patients being moved between sites will enable ambulance and patient transportation services to maintain focus on emergency response.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the number of first hospitalized patients per physician had a significant association with shortened LOS and a significant and positive association with increased medical service fees per day only indirectly. Previous studies have also shown that high-volume surgeons have a shorter LOS compared with low-volume surgeons [ 20 24 ]. High-volume surgeons, teaching hospitals, and high-volume hospitals are associated with improved outcomes when providing acute care for a variety of patient conditions and treatments [ 20 , 21 , 24 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the number of first hospitalized patients per physician had a significant association with shortened LOS and a significant and positive association with increased medical service fees per day only indirectly. Previous studies have also shown that high-volume surgeons have a shorter LOS compared with low-volume surgeons [20][21][22][23][24]. High-volume…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation